Lymph node ratio is an independent prognostic factor for rectal cancer after neoadjuvant therapy: A meta‐analysis. Issue 3 (11th July 2018) - Jin, Chengwu; Deng, Xiangbing; Li, Yan; He, Wanbin; Yang, Xuyang; Liu, Jian
Abstract: Objective: With neoadjuvant therapy increasingly used in advanced rectal cancer, the lymph node ratio (LNR) has been strongly considered to indicate cancer‐specific survival in recent years, and a comprehensive evaluation of a large number of studies is deficient. The objective of our study is to pool enough eligible studies to assess the relationship between LNR and prognosis of advanced rectal cancer after neoadjuvant therapy. Methods: A systematic search was done in the PubMed and EmBase databases (through 1 March 2017) that reported LNR in colorectal cancer after neoadjuvant therapy. The first two authors independently conducted the study selection and data extraction. All statistical analyses were conducted using STATA 13.0 (College Station, Texas). Results: Thirteen studies with 4023 participants were included in the meta‐analysis, and all were published after 2011. A high LNR was assessed to be a predictor of poor overall survival in rectal cancer after neoadjuvant therapy (HR: 2.94, 95% CI:1.97 to 3.91, P < 0.001). Similarly, a high LNR was related to poor disease‐free survival (HR: 2.83, 95% CI: 1.82 to 3.85, P < 0.001). With respect to recurrence, the HRs of 3.25, 1.93, and 2.11 also showed a strong relationship between high LNR and poor local, distant, and total recurrences. Conclusions: Our present study demonstrates that a high LNR can predict poor survival in advanced rectal cancer. We suggest well‐designed clinical trials to prospectively assess LNR as an independent predictor of rectal cancer survival.